(untitled) (diségno, 2025)
This article examines Bruno Munari’s contribution to visual communication, with a particular focus on his approach to graphic design and the graphic-visual language. The aim is to highlight how Munari redefined the processes of visual design by developing a method which, moving beyond a purely aesthetic perspective, integrates formal rigour, expressive synthesis and perceptual experimentation through a ‘structural’ exploration of how meaning is conveyed through images. The methodology adopted is based on a critical analysis of Munari’s major graphic works, enriched by theoretical references to semiotics, Gestalt theory and visual pedagogy. Through the examination of case studies –from the illegible books to editorial design and graphic experimentation for children– the study reveals the process by which Munari constructs an autonomous visual syntax, in which the graphic sign becomes a self-sufficient communication system. The purpose of this study is to demonstrate how Munari’s graphic thinking anticipated and influenced concepts that are now central to contemporary design and visual communication. His ability to transform illustration, typography and editorial graphics into tools for cultural and cognitive reflection makes him a key reference point in contemporary design, not only as a practitioner, but also as a theorist of a new visual grammar capable of transcending traditional conventions to create a universal, essential and immediate graphic language.